2014
DOI: 10.2355/isijinternational.54.2746
|View full text |Cite
|
Sign up to set email alerts
|

P2O5 Solubility Behavior and Resource Utilization of P-Bearing Slag

Abstract: In order to recycle the phosphorus in P-bearing steelmaking slag and make it used as slag phosphate fertilizer, the citric acid solubility of P-bearing steelmaking slag was researched. The research results show that the citric acid solubility of P-bearing steelmaking slag is decreased with the increasing of P2O5 and Fe2O3 content for the CaO-SiO2-Fe2O3-P2O5 slag system. Added CaF2 into slag can easily form the fluorapatite (Ca5(PO4)2F) that can't be dissolved in 2% citric acid solution, which makes citric acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Since the initial phosphorous content of the hot metal in such processes was higher than 1 wt% at the time, the final P 2 O 5 contents in slags typically ranged between 10 and 20 wt %. Recently, increased attention has being drawn again to this system due to the expected increase in the Phosphorous content of iron ores and subsequently, in the P 2 O 5 contents of the final slags . It was reported that when the Phosphorous content of hot metal is equal to 0.3 wt% or higher (which would be the case when high phosphorous iron ores are used), the P 2 O 5 content of the slag will be higher than 10 wt% .…”
Section: Discussion Of Ternary Oxide Systems Relevant To Bof Slagsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the initial phosphorous content of the hot metal in such processes was higher than 1 wt% at the time, the final P 2 O 5 contents in slags typically ranged between 10 and 20 wt %. Recently, increased attention has being drawn again to this system due to the expected increase in the Phosphorous content of iron ores and subsequently, in the P 2 O 5 contents of the final slags . It was reported that when the Phosphorous content of hot metal is equal to 0.3 wt% or higher (which would be the case when high phosphorous iron ores are used), the P 2 O 5 content of the slag will be higher than 10 wt% .…”
Section: Discussion Of Ternary Oxide Systems Relevant To Bof Slagsmentioning
confidence: 99%
“…Recently, increased attention has being drawn again to this system due to the expected increase in the Phosphorous content of iron ores and subsequently, in the P 2 O 5 contents of the final slags . It was reported that when the Phosphorous content of hot metal is equal to 0.3 wt% or higher (which would be the case when high phosphorous iron ores are used), the P 2 O 5 content of the slag will be higher than 10 wt% . For a proper evaluation of the state of phosphorous containing industrial slags, it is thus important to study the state of the CaO–FeO x –P 2 O 5 oxide system as well as the higher order systems based on it.…”
Section: Discussion Of Ternary Oxide Systems Relevant To Bof Slagsmentioning
confidence: 99%
See 1 more Smart Citation
“…J. Diao et al 9) and L. Lin et al 10) studied the solubility of P 2 O 5 from synthesized steelmaking slag in 2% citric acid. The dissolution ratio of P increased and reached 96% when Na 2 CO 3 was added to the slag during synthesis, which resulted from Na 2 Ca 4 (PO 4 ) 2 SiO 4 formation.…”
Section: Effects Of Acid and Na 2 Sio 3 Modification On The Dissolutimentioning
confidence: 99%
“…Recently, citric acid, which is often used to test the fertility of phosphate fertilizer and steelmaking slag, 15,16) has been shown to dissolve P more effectively than nitric acid by suppressing the precipitation of HAP. 17) This suppression occurs because the Ca cations form complexes with citrate in aqueous solution, decreasing the concentration of dissolved Ca below the solubility of HAP.…”
Section: Introductionmentioning
confidence: 99%